Ixchelia kochii (Violaceae, Rinoreeae), a new species from western Mexico and the third one of the genus - Guzmán, Ramón Cuevas; Rodríguez, Enrique V. Sánchez; López, Nora M. Núñez (Phytotaxa, 2019)
Ixchelia kochii Cuevas (Violaceae, Rinoreeae), a new species from western Mexico, is described and illustrated; it constitutes the third species of a recently described genus endemic to Mexico and Central America. The species grows in ecotones between tropical subdeciduous forest and montane cloud forest. The species of the genus are compared, and their relationships discussed.